Generation Alpha in the Era of Digital Radiation: A Literature Review on the Impact of Mobile Phone Exposure on Children's Health - Muhammad Fadli Ramadhansyah; Muhammad Aqmal Nurcahyo; Hanung Nurany; Ike Rachmawati; Intan Sekar Arumdani (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has made mobile phones an inseparable part of everyday life, including for Generation Alpha children. Although these devices provide educational and social benefits, exposure to the electromagnetic radiation they emit has the potential to cause various health impacts. Children are more vulnerable because their bodies are still growing and developing. This study aims to examine scientific findings related to the impact of mobile phone radiation exposure on the physical and psychological health of Generation Alpha children. A narrative literature review was conducted using 12 articles from databases such as Scopus, PubMed, ScienceDirect, MDPI, PlosONE, Google Scholar, and SINTA. The included articles were published between 2015 and 2025 and discussed the effects of electromagnetic radiation on children and adolescents. The results show that prolonged and unsupervised mobile phone use can affect visual function, sleep quality, and concentration, and may trigger digital addiction and psychological stress. Several studies also indicate possible long-term effects on the nervous system and hormonal balance. Exposure to mobile phone radiation in Generation Alpha children therefore requires serious attention, along with effective prevention and education strategies and further research to strengthen the evidence on its mechanisms and long-term impact on child development.